“Here Lies the Possibility of Bodies Turning Elemental”: - Jenny Andrine Madsen Evang (Kvinder, Køn & Forskning)
This paper explores the (non)representational aesthetics and politics of Serpent Rain, a 2016 Black feminist film inspired by the recovery of a Danish-Norwegian slave ship. Despite ample historical evidence, Scandinavia’s involvement in the transatlantic slave trade remains an underdiscussed topic; when the history is broached at all, it tends to be relegated to a distant ‘dark chapter’ already overcome. I argue that Serpent Rain rejects this binary of erasure vs. contained representation in its treatment of slavery, enacting instead another type of (non)representation that moves beyond “the limits of most available narratives to explain the position of the enslaved” (Hartman and Wilderson 2023, 184). Taking its meandering and associative form from Serpent Rain’s experimental aesthetics, this article draws on Black feminist theory—particularly Christina Sharpe’s In the Wake—to argue that the film unsettles visual and ontological certainty to dramatize the repetitive structure of racial capitalism and its ongoing reiterative violence, from the sunken slave ship to the ongoing extraction of oil on indigenous land. Ultimately, the film makes us question not only the hegemonic mediation of the enslaved, but also the orthography of the (white) Human and the seeming serenity of Norwegian oceanic landscapes.